Global governance and biopolitics : regulating human security - Roberts, David W. (David Wesley), 1962- (Zed Books, 2010)
This seminal work is the first fully to engage human security with power in the international system. It presents global governance not as impartial institutionalism, but as the calculated mismanagement of life, directing biopolitical neoliberal ideology through global networks, undermining the human security of millions. The book responds to recent critiques of the human security concept as incoherent by identifying and prioritizing transnational human populations facing life-ending contingencies en mass. Furthermore, it proposes a realignment of World Bank practices towards mobilizing indigenous provision of water and sanitation in areas with the highest rates of avoidable child mortality. Roberts demonstrates that mainstream IR's nihilistic domination of security thinking is directly responsible for blocking the realization of greater human security for countless people worldwide, whilst its assumptions and attendant policies perpetuate the dystopia its proponents claim is inevitable. Yet this book presents a viable means of achieving a form of human security so far denied to the most vulnerable people in the world.